Nursing Faculties: The Heart of Nursing Academia (Purbanchal University Health Journal, 2024)
Nursing academics involves both the profession of nursing and the profession of education. This article sheds light on different duties and responsibilities performed by nursing faculties, various challenges, and how nursing institutions and stakeholders can work together to overcome the challenges. This article also focuses on various key areas like research, clinical practice, teaching-learning activities, and administrative roles that nursing faculties are supposed to acquire and gain their competence. Moreover, nursing faculties plays pivotal role in tailoring the quality nursing professionals. However, faculties need to attain excellence in their roles so that the positive attitude with professional demeanor are passed on to the next generation.